The effect of music therapy on dental anxiety of patients seeking tooth extraction from the University of the Philippines Manila, College of Dentistry (UPM-CD) clinic - Gutierrez, Emelee Jean G.; Lim, Jenina Marian U.; Jimena, Edna M.+(Co-author).; Santos, Jessica K.R. (Adviser).
Music has been widely utilized in various fields of health science for its healing properties. Studies have shown its effectiveness in relation with medical and dental fields. Objective: This study aimed to determine the effect of music therapy on dental anxiety of patients seeking tooth extraction in UPM-CD clinic. Participants: Twenty-two patients indicated for molars extraction were selected as participants. They were healthy adults whose ages range from 20-40 years old. Methodology: The blood pressure and heart rates were recorded using a digital BP monitor pre-operatively, during and after the procedure. For the control group, treatment was done without music while the experimental groups was subjected to soft and quiet music all throughout the procedure with the use of an iPod and speakers. Results: It was shown that the study population had moderate anxiety level. The group with music had lower mean blood pressure and mean heart rate records than the group without music. Patient's perception on the music used was that they liked it and they were able to tell that somehow, the music helped in decreasing their anxiety. Conclusion: Applying soft and quiet type of music can decrease the level of anxiety during extraction procedures as physiological indicators of anxiety (blood pressure and heart rate) were lower in the experimental group. Soft and quiet music can be beneficial for patients who will undergo tooth extraction.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentistry - Psychological aspects; Music therapy - Health aspects